2015
DOI: 10.5901/ajis.2015.v4n1s2p139
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training Program on Physical Characteristics and Social Development of Boys

Abstract: Sport is important for physical and social development of children. Through sports, recognition of the environment and communication with his/her environment takes place more easily for children. The aim of this research was to examine the effects of regular physical activity on physical and social developments of boys at 11 ages. The population of the study consisted of 11-years-old children. The sample group consisted of 10 children who want to participate in training and signed permission documents by their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…In specific sports, handball studies [37][38][39] , are found within this theme. In the population with school practitioners and health context, the study with the closest theme demonstrated effectiveness in the BMI variable, with a difference between the pre and post-test averages, but we do not have a significant probability 40 . Inside health, interventions aimed at preventing injuries to adolescent athletes through strength training have proven effective in protecting the athlete's health and physical integrity 41,42 .…”
Section: Discussioncontrasting
confidence: 54%
“…In specific sports, handball studies [37][38][39] , are found within this theme. In the population with school practitioners and health context, the study with the closest theme demonstrated effectiveness in the BMI variable, with a difference between the pre and post-test averages, but we do not have a significant probability 40 . Inside health, interventions aimed at preventing injuries to adolescent athletes through strength training have proven effective in protecting the athlete's health and physical integrity 41,42 .…”
Section: Discussioncontrasting
confidence: 54%
“…In line with studies based on adult players, research with children has tend to relate to general motor skills e.g. Ingebrigsten & Jeffreys (2012); Ingebrigsten, Rodahl & Jeffreys, (2013); Zhunisbek et al, (2016); Broderick & Newell (1999); Karadenizli (2016); Kayapinar et al, (2015). Only a few studies have been conducted to consider effect of handball on improving motor skills in children, albeit tenuously, as it was mainly a physical characteristics study (Ion, 2015;Juhász et al, 2016;.…”
Section: Handball Specific Researchmentioning
confidence: 72%
“…Several Hungarian and international researches have dealt with the testing and choice of adult handballers (Granadoset al 2007;Nikolaidis and Ingebrigtsen 2013;Serrien et al 2016, Schweising et al 2016Gürhan et al 2016;Sabido et al 2016König and Ökrös 2016;König et al 2017), and the importance of ICT in education (Czeglédi 2007(Czeglédi , 2008Nagy and Müller 2016 a,b;Nagy et al 2017). Researches dealing with the measurement of children playing handball at school age also have literature background (Ingebrigtsen and Jefferys 2012;Diana et al 2016;Karadenizli 2016;Muratovic et al 2015;Kayapinar et al 2015;Ingebrigtsen et al 2013). Role of conditional abilities, mental stamina and performance indicators of adult elite sportsmen has also been examined by several professionals (Rivilla et.…”
Section: Discussionmentioning
confidence: 99%